EVALUATION OF TOURISM MARKETING COMMUNICATIONS PUNCAK SOSOK AS DESTINATION OF NIGHT TOURISM IN BANTUL - Estavita Chantik Pembayun; Yenni Sri Utami; Isbandi Sutrisno (The Indonesian Journal of Communication Studies, 2020)
As a night tourist destination that is unique and has great potential, Puncak Sosok requires an evaluation of Puncak Sosok's marketing communications. The formulation of the problem in this research is how to evaluate marketing communication conducted by Puncak Sosok managers. The purpose of this research is to describe and to find out the evaluation of Puncak Sosok marketing communication and the supporting and inhibiting factors in its implementation. This research uses eight main marketing communication models by Kotler and the PII (Preparation, Implementation, Impact) evaluation model by Cutlip-Center-Broom with a qualitative approach. The results of the evaluation on the preparation aspect are conformity with the objectives and background where fluctuations in visits, but there are no details number of the tourist targets so that the measurement of success is not detailed. Evaluation on the implementation aspect are that most of the programs have been running well, but there are problems such as social media creativity and the absence of tour packages and authentic Puncak Sosok products. Impact evaluation results on most programs have had a positive impact such as the number of media publications and known as a typical night tourism destination with live music. Nevertheless, some programs are still ineffective and need to be improved, such as direct marketing and personal selling programs, which have less impact on attracting tourists. Supporting factors are the relationship that exists with the media and stakeholders, while the lack of innovation and knowledge of human resources in marketing and media use become inhibiting factors.